Short-term biochar amendment enhances the chemical stability of soil organic carbon in the labile pools but may inhibit native SOC transformation into stable pool - Jinsuo Li; Zhaofeng Chang; Genghao Zhang; Luping Tian; Qu Wenhao; Peng Zhang; Kai Liu; Weiying Hou; Bo Pan (Soil and Tillage Research, 2026)

Correction: Cell-free mitochondrial DNA as a potential predictor for hypoxic stress - Qiaoping Qu; Can Xiao; Xuemei Liu; Aixue Huang; Hui Li; Gang Xu; Ningsheng Shao; Yuechao Zhao; Bo Gao (Molecular Biology Reports, 2026)

Cell-free mitochondrial DNA as a potential predictor for hypoxic stress - Qiaoping Qu; Can Xiao; Xuemei Liu; Aixue Huang; Hui Li; Gang Xu; Ningsheng Shao; Yuechao Zhao; Bo Gao (Molecular Biology Reports, 2026)

Interpretable machine learning-based prediction and optimization of per- and polyfluoroalkyl substances chain length-dependent adsorption behavior on porous carbon materials with experimental validation - Yueheng Jiang; Bo Wei; Xiaoqiang Cao; Yanling Qu; Yang Zhang; Yujiao Kan (Journal of Environmental Chemical Engineering, 2026)

A memory-constrained multiscale pore network modeling framework for gas permeability prediction in compacted bentonite - Yongxiao Qu; Huaxiang Yan; Bo Li; LiGe Wang; Andrey P Jivkov; Weiguang Wang; Lin Ma; Mohsen Masihi; Qingrong Xiong (Computers and Geotechnics, 2026)

Recent advances on MXene nanomaterials-based biosensing technologies and portable analytical devices for detection of food hazard factors - Haofang Liu; Ling Li; Biru Han; Yina Zhao; Manyan Qiu; Qianyu Zhao; Bo Qu; Xianlong Zhang; Yujun Jiang (Trends in Food Science & Technology, 2026)

Dynamic changes in structural characteristics and biological activities of polysaccharides from Lentinus edodes during postharvest storage - Ru Li; Zhihan Zheng; Yilong Zou; Jingxiao Li; Yi Wu; Hailong Yang; Hang Qu; Bo Chen (Postharvest Biology and Technology, 2026)

Research on fracture propagation characteristics and design optimization of well factory fracturing in laminated shale reservoirs - Bo Zhang; Yanlong Li; Tiankui Guo; Nengyou Wu; Minhui Qi; Jiwei Wang; Zhanqing Qu (Geomechanics for Energy and the Environment, 2026)

Carbohydrate polymer-based nanoarmor systems for probiotic gastrointestinal delivery: Strategies, applications, and perspectives - Zhuan Song; Yina Zhao; Xiaofeng Hu; Xiaorong Liu; Mingshuang Sun; Yuhang Tian; Bo Qu; Xianlong Zhang; Yujun Jiang (Carbohydrate Polymers, 2026)

Comprehensive epigenetic landscape of Sulfur Mustard (SM) exposure in HaCaT keratinocytes - Yuejia Du; Bo Ma; Yuanjie Li; Yanli Zhu; Zhi Li; Minmin Qu; Qinyun Shi; Weiwei He; Jia Chen; Bin Xu; Jie Li; Wenqi Meng; et al. (Chemico-Biological Interactions, 2026)

Role of pyroptosis in melanoma: Molecular mechanisms and therapeutic potentials - Xiao-Han Zhang; Ke Zhang; Xue-Chun Qu; Jing Zhang; Umm E. Laila; Bo Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2026)

SIRT1 overexpression derived by NSUN2-mediated m5C methylation alleviates tenogenic injury of human tendon-derived stem cells - Bo Zhu; Shaoli Liu; Hao Gu; Dongmei Ding; Dongjing Qu; Jingtian Liu (Tissue and Cell, 2026)

Fungal community succession drives the decay of jujube fruit (Ziziphus jujuba Mill. cv. Jingcang 1) during ambient storage - Jian-Yu Wang; Ke-Xin Jiao; Min-Xin Mao; Cheng-Gang Li; Jian-Ping Qu; Bo Zhou; Qian Zhang; Qing Hao (Postharvest Biology and Technology, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

Lactic acid-mediated chitosan/starch complexation: A green strategy for synergistically enhancing resistant starch content and sensory quality in lotus root starch-based foods - Jihong Qu; Yi Liu; Jiadong Li; Haibo Zhao; Jianpeng Li; Die Dong; Chao Yuan; Meng Zhao; Bo Cui (Carbohydrate Polymers, 2026)

Enhancing GRACE/GFO spatial downscaling accuracy via graph convolutional networks: a comparative study and ecological response analysis in the Pearl River basin - Yuheng Lu; Lilu Cui; Bo Zhong; Chuanjiang Luo; Haoyang Guo; Xiaochuan Qu (Computational Geosciences, 2026)

Emeishan basalt’s contribution to heavy metals in topsoil (notably cadmium) in Southwest China from soil geochemistry evidence - Fang Yang; Liang Tang; Yang Li; Bo Cheng; Tim T. Werner; Lingfei Qu; Ke Cheng; Aiming Zhang; Junbo Wang; Guikai Li (Acta Geochimica, 2026)

Tuning electron transfer and surface dual-sites for synergistic peroxymonosulfate activation toward efficient 2,4,6‑trichlorophenol degradation - Jingyi Wang; Yitong Liu; Wenhui Qiu; Lin Zhang; Kaige Li; Ran Wang; Bo Cao; Jianhua Qu; Ying Zhang (Process Safety and Environmental Protection, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

A review of early Paleozoic subduction-accretion tectonics in the North Qilian Orogenic Belt, Northeastern Tibet: Implications for the evolution of the Proto-Tethys Ocean - Dong Fu; Bo Huang; Timothy Kusky; Simon A. Wilde; Fengyu Qi; Xiaoxue Shan; Yilin Qu; Hong Wang (Earth-Science Reviews, 2026)

A novel nonlocal damage model for fluid-driven mixed-mode fracture propagation in poroelastic medium - Changxin Yang; Cheng Ma; Jianhua Qu; Zhaozhong Yang; Xin Yang; Bo Kang; Duo Yi (Computers and Geotechnics, 2026)

A critical review of biochar adsorption mechanisms and performance in soil remediation of perfluoroalkyl and polyfluoroalkyl substances - Xue Pan; Bo Yang; Fanhua Meng; Yufang Wei; Wenbing Tan; Kunlong Hui; Chengtun Qu; Chen Shen; Beidou Xi (ENGINEERING Environment, 2026)

Influence Mechanism of Complex Natural Fractures on Fracture Propagation of Multi-well Fracturing in Laminated Shale Reservoirs: A Numerical Study - Tiankui Guo; Bo Zhang; Ming Chen; Yanlong Li; Yongzan Liu; Fengshou Zhang; Nengyou Wu; Zhanqing Qu (Rock Mechanics and Rock Engineering, 2026)

AI in cheese manufacturing: A comprehensive review of technologies, applications, and future prospects - Nuo Xu; Biqi Liu; Renyi Geng; Yu Zhang; Xinyan Yang; Wei Zhang; Bo Qu; Ling Guo; Yujun Jiang (Trends in Food Science & Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Two new diterpenoids isolated from Siegesbeckia pubescens and their in vitro anti-inflammatory activities - Mei-Hui Zhou; A-Jiao Hou; Ling-Xia Qu; Jin-Bo Li; Liu Yang; Hai Jiang (Phytochemistry Letters, 2026)

N-doped porous hydrochar supported magnesium ferrite for efficiently eliminating lead and tetracycline from the soil environment - Jianhua Qu; Wenqi Zhang; Qinghua Zheng; Youjie Xu; Linyu Xu; Bo Cao; Yue Tao; Tianqi Liu; Ying Zhang (Journal of Environmental Chemical Engineering, 2026)

Construction of a Ni/Semi-coke catalyst via a NiCl2-Lactic acid deep eutectic solvent for upgrading coal pyrolysis tar - Haozhao He; Tao Wang; Qu Zhang; Bo Li; Xianze Wang; Wenyan Mu; Dongling Wu (Fuel, 2026)

Employing L-cysteine-mediated modulation for nickel biorecovery: Bioseparation-photocatalytic upcycling from wastewater - Shunling Li; Peng Cui; Zhaosheng Zhang; Fenxiang Li; Pan Bo; Qing Qu (Environmental Research, 2026)

High-efficiency solar-driven photothermal membrane distillation via permeate-side interfacial heating - Qian Yu; Mengfei Xie; Rong Chen; Kuiling Li; Liqiu Zhang; Bo Pan; XueJun Pan; Junhui Zhang; Dan Qu (Desalination, 2026)

Janus tissue adhesive patches with antibacterial drug delivery and visceral anti-adhesion capacity for gastrointestinal anastomosis repair - Xuguang Jiao; Shenshuo Gao; Hongyang Li; Junyan Yang; Siqi Liu; Wei Jing; Bo Zhao; Pengfei Wei; Yiqian Huang; Jianjun Qu (Chemical Engineering Journal, 2026)

Optimizing biochar selection for soil amendment: Unraveling the feedstock-texture interplay for enhanced crop performance - Rong Zhang; Zizhen Ma; Linhua Jiang; Wenjie Gao; Hongping He; Heng Yu; Tao Yu; Bo Yang; Chengtun Qu (Bioresource Technology, 2026)

Integrated multi-omics and experimental validation for identifying novel biomarkers of acute myocardial infarction - Siyuan Qu; Qi Nie; Jiaxi Li; Bo Zhang; Ziqiang Chen; Liya Zhou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Unraveling spatiotemporal inequalities and nonlinear drivers in the sustainable transition of cultivated land use: Evidence from the Yangtze River Delta region, China - Shilei Wang; Xiaobin Jin; Yanbo Qu; Yeting Fan; Jing Liu; Bo Han; Yinkang Zhou (Applied Geography, 2026)

A numerical study of damage evolution and crack propagation in backfill bodies of high-temperature thermal energy storage cavities in mines - Rui Zhan; Bo Zhang; Lang Liu; Chao Huan; Huisheng Qu; Huicong Xu; Jin Zhang; Hongjun Xi (Tunnelling and Underground Space Technology, 2026)

Effect of flow conditions on solid-liquid two-phase flow characteristics in the multistage deep-sea mining pump - Leilei Ji; Jie Yang; Wei Li; Weidong Shi; Xinrui He; Yang Yang; Ling Zhou; Fei Tian; Bing Qu; Bo Pan; Ramesh K. Agarwal (Ocean Engineering, 2026)

Determination of dissociation constants between single-protein and multicomponents by a multi-chamber membrane separation electrophoresis system as a complementary tool - Hai-Bo Shang; Yuwei Zhu; Yonglong Liu; Lei Yang; Yanying Qu; Meiyu Cui; Meihua Dong; Xiangfan Piao; Donghao Li (Analytica Chimica Acta, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Chrysovirus BbCV1 confers enhanced sporulation and environmental fitness to Beauveria bassiana - Lili He; Guogen Yang; Ping Wang; Yang Yang; Jiaojiao Qu; Bo Huang (Pesticide Biochemistry and Physiology, 2026)

Interfacial synergy-enhanced catalysis in hierarchically confined poly (glycidyl methacrylate) @ZIF-8@Au composite microspheres for p-nitrophenol degradation - Jian-Bo Qu; Guo-Yu Yue; Jian-Ling Zhang; Yuan Yang; Dong Wang; Jia-Le An; Jing Li (Journal of Environmental Chemical Engineering, 2026)

Fabrication of chitosan/alginate/angelica polysaccharide functional microcapsules: enhancing the viability of Lactobacillus paracasei in digestion, storage and applications - Haifu Jia; Jinghang Zhang; Yuanyuan Li; Zhishan Song; Yatong Ni; Bo Qu; Xinyan Yang; Qianyu Zhao; Yujun Jiang (Food Hydrocolloids, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Surfactant-mediated sub-nanostructure engineering of morphology-tailored magnesium fluoride derivatives for resistant bacterial wound repair - Xiaoyan Qu; Yumeng Shen; Kunkun Nie; Luyao Guo; Bo Lei; Zhengqing Liu (Chemical Engineering Journal, 2026)

Time-varying tensile resistance mechanisms in slope-protecting alfalfa roots - Xu Duan; Zikang Yang; Bo Wang; Chuangchuang Chen; Jin Qu; Yuan Chang; Luyu Shi; Hanyang Yan; Qi Dong; Wanjun Ye (Plant and Soil, 2026)

Adaptation Mechanisms of Aquatic Animals to Saline–Alkaline Water Aquaculture: Physiological, Energetic and Molecular Perspectives - Yingsha Qu; Huichen Li; Bo Zhang; Hongwu Cui; Jianlei Chen; Yong Xu; Zhengguo Cui; Keming Qu; Hao Li (Fishes, 2026)
Saline–alkaline water constitutes a vital strategic non-traditional fishery resource in China, characterized by high pH values, elevated carbonate alkalinity, and complex ionic compositions. These extreme environmental conditions impose significant stress on aquatic animals, mainly by inducing ionic toxicity and disrupting acid–base regulatory mechanisms. Such disruptions subsequently lead to osmotic imbalance, metabolic dysregulation, and immunosuppression, thus restricting the survival and growth of aquatic species in aquaculture systems. Consequently, the sustainable development of the saline–alkaline aquaculture is imperative for enhancing production efficiency and promoting the utilization of marginal land and water resources. This review comprehensively summarizes the current status of saline–alkaline aquaculture and highlights the stress-inducing impacts of salinity, alkalinity, and specific ionic ratios on teleost fishes and crustaceans. It further explores key adaptive mechanisms, including osmoregulatory and ionoregulatory strategies, bioenergetic trade-offs related to oxygen consumption and ammonia excretion, coordinated antioxidant and innate immune responses, as well as recent findings from multi-omics research. This review aims to offer a scientific foundation for the selection and breeding of saline–alkaline-tolerant strains, the precise regulation of aquaculture water environments, and the development of ecological aquaculture models in saline–alkaline regions, thereby facilitating the sustainable utilization of saline–alkaline land and water resources.

Deterioration characteristics of red beds lithological interface under water-rock interaction and its influence on tunnel deformation - Jingkai Qu; Yiguo Xue; Fanmeng Kong; Cuiying Zhou; Jianbing Peng; Su Yan; Zhen Liu; Zhuang Ruan; Mingdong Zang; Kang Fu; Bo Wang; Minghao Jia; et al. (International Journal of Rock Mechanics and Mining Sciences, 2026)

Impacts of small herbivore disturbance on grassland ecosystem multifunctionality on the Qinghai-Tibetan Plateau - Zhaoxian Tan; Baohui Yao; Rong Wang; Yihong Wang; Bo Fan; Yan Zhang; Xinyan Chen; Jianzhuo Feng; Jiapeng Qu (Journal of Mountain Science, 2026)

Distribution Characteristics of Sediment Iron Under Different Hydrological Connectivity in a Brackish Water Zone of the Yellow River Delta, China - Xue Li; Bo Guan; Junbao Yu; Eller Franziska; Jisong Yang; Di Zhou; Yunzhao Li; Xuehong Wang; Xin Zhang; Chenyu Qu; Jifeng Guo (Chinese Geographical Science, 2026)

Water inrush risk assessment during karst tunnel construction based on knowledge decision and data-driven methods - Xuewei Li; Shuchen Li; Bo Wang; Jiaxin Qu; Jinlong Zhao; Shisen Zhao (Tunnelling and Underground Space Technology, 2026)

RSM-based development and optimization of a novel fracture sealing material for secondary grouting in extraction boreholes - Junxiang Zhang; Yijian Guo; Bo Li; Yadong Bian; Shumin Ding; Lina Qu; Zhenfeng Wang; Yaocai Tang; Pan Chen (Fuel, 2026)

Study on the effect of glycosylation reaction in wet mixing on the emulsifying properties of extensively whey protein hydrolysates - Zhen Huang; Lidong Pang; Runze Li; Jia Shi; Qianyu Zhao; Yujun Jiang; Xinyan Yang; Bo Qu (Food Chemistry, 2026)

Quorum sensing enhanced dissimilatory nitrate reduction to ammonia processes in constructed wetland-microbial fuel cells - Shuyuan Zhao; Jun Yan; Mengli Chen; Fucheng Guo; Wen-bo Nie; Jun Li; Han Qu; Yi Chen (Bioresource Technology, 2026)

Comparative Analysis of the Climate in the Barents Sea and Greenland Sea for a Perturbation of the Sea-to-Air Flux of Dimethylsulfide - Guangsheng Zhong; Bo Qu (Journal of Ocean University of China, 2026)

Modeling wave attenuation in salt marshes under variable vegetation and wave conditions using XBeach model with a new parameterization scheme - Bingchen Liang; Xuedong Wu; Hong Zhang; Zhipeng Qu; Bo Yang; Guoxiang Wu (Ocean Engineering, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

Distribution, contamination and source discrimination of heavy metals in sediments from dam reservoir at Changsha city along the Xiangjiang River, China - Xia Yang; Bo Peng; Sicheng Wu; Nengqiu Wu; Hongjie Hu; Xianjia Du; Yunhan Qu; Yanan Dai; Xin Wang (Environmental Geochemistry and Health, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

Two new compounds from the roots of Mirabilis jalapa L. and their cytotoxic activity in vitro - Xiao-Mei Yan; Tian-Tian Qu; Jie Luan; Hou-Run Zhang; Xiang-Qin Tang; Xiao-Xu Bi; Ying Wang; Bing Chen; Jiang-Bo He (Phytochemistry Letters, 2025)

O-Hf-Mg isotopic signals of recycled oceanic crust in the Early Cretaceous I-type granites from NE China - Ao Li; Wu-Bin Yang; Xu Zhao; He-Cai Niu; Ning-Bo Li; Pan Qu (Lithos, 2025)

Epidote U–Pb geochronology reveals staged skarn formation linked to geodynamic transformations in convergent continental margins - Shuang Yan; Wu-Bin Yang; Ning-Bo Li; Pan Qu; He-Cai Niu (Geochimica et Cosmochimica Acta, 2025)

Positively charged components (chitosan most potently) combined with annealing: Modulating digestibility and viscosity of corn starch - Yi Liu; Jihong Qu; Haibo Zhao; Jianpeng Li; Die Dong; Chao Yuan; Meng Zhao; Bo Cui (Food Bioscience, 2025)

Sprayable and scalable superhydrophobic passive daytime radiative cooling coating for sub-ambient temperature regulation - Chengjie Qu; Qingqing Lu; Bo Wang; Jinyue Song; Ziye Han; Xingxiang Ji; Zuankai Wang; Libin Liu (Energy and Buildings, 2025)

Characterization of a novel biosurfactant from Alcanivorax dieselolei and its mechanism for enhanced oil recovery in low-permeability reservoirs - Shuyuan Deng; Bo Wang; Ruixue Qu; Yuxiao Han; Cenqian Zhang; Chenyue Wang; Jian Fu; Shanshan Sun; Hao Dong; Gongze Cao; Qing You; Yuehui She; et al. (Chemical Engineering Journal, 2025)

Deep eutectic solvent-enzyme synergistic pre-treatment strategy for the preparation of cottonseed meal-based porous carbon for advanced supercapacitors - Qu Zhang; Tao Wang; Yan Ma; Pengxu Ren; Bo Li; Yinying Wang; Lina Peng; Dongling Wu (Chemical Engineering Journal, 2025)

Main Controlling Factors of Imbricate Thrust Faults at the Frontal Edge of the Makran Accretionary Wedge–Insights from Physical Simulations - Bo Sun; Fusheng Yu; Jing Liao; Jianming Gong; Jiajie Yan; Wenhao Lei; Jiajun Qu; Haoyue Sun; Zixuan Cui; Jia Ren (Journal of Ocean University of China, 2025)
The frontal edge of the Makran accretionary wedge is characterized by the development of multiple imbricate thrust faults trending E-W and relatively parallel. However, the mechanisms underlying their formation and the factors controlling their development remain subjects of debate. This paper, based on seismic profile analysis, employs physical simulation experiments to establish a ‘wedge’ type subduction model. The study explores the influence of the initial wedge angle, horizontal sand layer thickness, and the presence or absence of a decollement layer on the structural styles of the thrust wedge. Experimental results indicate that as the initial wedge angle decreases from 11° to 8°, the lateral growth of the thrust wedge increases, whereas vertical growth diminishes. When the horizontal sand layer thickness is reduced from 4.5 cm to 3.0 cm, the spacing between the frontal thrusts decreases and the number of thrust faults increases. Both lateral and vertical growth are relatively reduced, resulting in a smaller thrust wedge. When a decollement layer is present, the structural style exhibits layered deformation. The decollement layer constrains the development of back thrusts and promotes the localized formation of frontal thrusts. In conclusion, the imbricate thrust faults at the frontal edge of the Makran accretionary wedge are primarily controlled by the characteristics of the wedge itself and the presence of the decollement layer.

Chemical constituents and bioactivities of fermented rose (from Yunnan ) extract - Bo Peng; Yining Hao; Yueyue Chen; Shishuai Yu; Liping Qu (Natural Product Research, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Oyster culture and hydrological characteristics regulate the distribution and accumulation of sedimentary organic matter in two subtropical mariculture areas - Bo Yang; Yi Qu; Bin Yang; Rongliang Zhang; Mai Li; Yifei Zhang; Yuchen Liu; Lei Xie; Qin Li; Zhenjun Kang; Guodong Song (Journal of Hydrology, 2025)

Pyrococcus furiosus Argonaute biosensing platform based on Hemin@ZIF-90 nanozyme-modulated signal amplification for sensitive detection of Salmonella typhimurium - Xiru Zhang; Manyan Qiu; Yiyi Zhang; Qianyu Zhao; Bo Qu; Wei Zhang; Xianlong Zhang; Yujun Jiang (Food Chemistry, 2025)

miR-133b regulation of wbp2 in ovaries is conserved among teleosts - Jiayu Zhou; Qianwen Min; Xubing Ba; Zhaoqiu Qu; Zhenjun Zhuang; Biao Yuan; Xin Yi; Ruojing Li; Na Zhao; Bo Zhang (Acta Oceanologica Sinica, 2025)

Corrigendum to “WWOX attenuates the progression of gallbladder cancer by suppressing cellular glycolysis through the modulation of the P73/HIF-1a signaling pathway” [Tissue Cell 95 (2025) 102885] - Bo Tang; Qi-Cai Qu; Dong-Yun Cun; Xia-Wei Yang; Kun Su; Ren-Chao Zou; Tao Wang; Lian-Min Wang; Tao Wu; Dong Wei; Qiu-Hong Wang (Tissue and Cell, 2025)

An adaptive recognition method for crop row orientation in dry land by combining morphological and texture features - Xingming Zheng; Jia Zheng; Xigang Wang; Fuheng Qu; Tao Jiang; Zui Tao; Bo Zou; Shixu Song; Tianyu Ding (Soil and Tillage Research, 2025)

In-situ remediation efficiency and mechanism of tylosin contaminated soil with biochar immobilized degrading enzyme - Bo Zhang; Xiaoying Hu; Zhen Guo; Jianhua Qu; Yuze He; Lu Han; Juntong Kou; Hongqi Yu; Jiuxuan Lian; Ying Zhang (Journal of Hazardous Materials, 2025)

Oxidative polymerization of PEDOT in YMOF-NH2 framework for electrochemically controlled phosphate removal and enrichment - Zhuangzhuang Bi; Zhangjie Huang; Guang Li; Yuanyuan Guo; Qing Qu; Bo Wu (Journal of Environmental Chemical Engineering, 2025)

Amphiphilic block copolymer-based fire suppression material – Study on coal spontaneous combustion prevention and extinguishing performance - Gang Zhou; Hongrui Qu; Bo Wei; Tianrui Niu; Yongmei Wang; Xiaosu Dong; Rulin Liu; Lin Li; Shuailong Li (Journal of Environmental Chemical Engineering, 2025)

Study on processability, hydration characteristics and solidification mechanism of hazardous elements of high-phosphorus solid waste paste backfill materials - Yandong Han; Lang Liu; Shishan Ruan; Mengbo Zhu; Bo Yu; Huisheng Qu; Chengcheng Shao; Tiantian Li (Journal of Environmental Chemical Engineering, 2025)

Exploring the functional diversity of wild Saccharomyces cerevisiae strains for breadmaking applications - Chenwei Pan; Jiaming Li; Tianzhi Qu; Hui Liu; Weiming Xiao; Bo Chen; Anqi Chen; Jian Chen (Food Bioscience, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Recent advances in nanomaterial biosensors for the detection of antibiotics to ensure food safety - Bo Long; Qian Zhang; Lintong Zhang; Qiongqiong Xing; Qi Liu; Liying Deng; Fangfang Qu; Rui You; Xuan Wei; Dapeng Ye; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Nitrogen utilization in response to cadmium and abscisic acid in rice - Zhi-Jun Xu; Jia-Yi Qu; Meng Zhao; Jing Zhao; Wei-Chi Wang; Jia-Jun Huang; Jia-Shi Peng; Yun-Hua Xiao; Yong-Liang Han; Yan Peng; Bo-Han Liu; Zhen-Xie Yi; et al. (Plant and Soil, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

WWOX attenuates the progression of gallbladder cancer by suppressing cellular glycolysis through the modulation of the P73/HIF-1α signaling pathway - Bo Tang; Qi-cai Qu; Dong-yun Cun; Xia-wei Yang; Kun Su; Ren-chao Zou; Tao Wang; Lian-min Wang; Tao Wu; Dong Wei; Qiu-hong Wang (Tissue and Cell, 2025)

Bioaugmentation strategies for polycyclic aromatic hydrocarbons–contaminated intertidal zones: Effects and microbial community succession - Jiawei Jing; Bo Zhao; Tingting Wang; Pengfei Huang; Chuan Li; Xinyu Guo; Yuanyuan Qu (Journal of Hazardous Materials, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Taurine related pathways effect the potential domestication of wild Larimichthys crocea adapt to stress environment - Xubing Ba; Zhenjun Zhuang; Zebin Zhou; Jiayu Zhou; Qianwen Min; Biao Yuan; Xin Yi; Ruojing Li; Zhaoqiu Qu; Na Zhao; Bo Zhang (Aquaculture, 2025)

Allicin fumigation delays the decline of fruit quality in blueberries via regulation of reactive oxygen species - Siyu Long; Bo Xu; Yating Zhang; Yingchao Qu; Shujuan Ji; Manli Luo; Meilin Li; Bing Bai; Qian Zhou (Postharvest Biology and Technology, 2025)

Red Emissive Carbon Dots as Fluorescent Probe for Specific Sensing and Imaging of HCIO - Ying Peng; Haonan Yang; Mengyao Qu; Shaobing Zhang; Zheng Yang; Xiaodan Jia; Bo Wang; Xiangrong Liu (Journal of Fluorescence, 2025)

Heat-triggered CRISPR/Cas12a microspheres for one-pot assays - Siying Xie; Shan Shao; Jin Wang; Jing Qu; Ying Cai; Xingyan Lai; Nan Min; Lidan Zhang; Yan Shi; Tingdong Li; Xiaomin Zhang; Bo Peng; et al. (Science Bulletin, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Preparation and performance of Zr-Si based ultra thermal-insulating ceramic aerogels inspired by alpaca wool under extreme temperatures - Gang Zhou; Xiuhui Qu; Linquan Tong; Bo Wei; Yunli Sun; Zonglei Mou; Qi Zhang; Seeram Ramakrishna; Qunzhi Meng (Chemical Engineering Journal, 2025)

Rutin Attenuates Distraction Spinal Cord Injury by Inhibiting Microglial Inflammation Through Downregulation of P38 MAPK/NF-κB/STAT3 Pathway - Junrui Jonathan Hai; Weishi Liang; Duan Sun; Peng Yin; Bo Han; Xianjun Qu (Molecular Neurobiology, 2025)

Small molecule carbon sources drivers increase in heavy metal passivation during chicken manure composting by regulating microbial functional and metabolic pattern - Qinghong Sun; Chenshu Ming; Zhao Jiang; Bo Cao; Jianhua Qu; Ying Zhang (Journal of Environmental Management, 2025)

Potential genetic markers of biofilm formation ability by Listeria monocytogenes isolated from fresh agricultural products - Jing Wang; Qingli Dong; Xiujin Chen; Bo Feng; Yang Qu; Ting Lin; Yalong Bai; Peihong Liu; Changyan Zhou; Yujuan Suo (International Journal of Food Microbiology, 2025)

Integration of network toxicology and transcriptomics reveals the novel neurotoxic mechanisms of 2, 2′, 4, 4′-tetrabromodiphenyl ether - Tengjiao Qu; Qian Sun; Bo Tan; Hao Wei; Xiaoxuan Qiu; Xiaojie Xu; Hui Gao; Shun Zhang (Journal of Hazardous Materials, 2025)

Microwave-assisted synthesis of a β-cyclodextrin/TEMPO-oxidized cellulose/Fe3O4 adsorbent for Pb and Cu remediation in soil - Siqi Wang; Mengning Wang; Haowei Wu; Xiaoqi Sun; Zonghao Dong; Wei Peng; Bo Zhang; Chen Cai; Jianhua Qu (Journal of Cleaner Production, 2025)

The influence of potential source parameters of novel near-fault synthetic ground motions on nonlinear cross-stream seismic response for high-arch dams based on conditional mean spectrum - Tianran Zhang; Qiang Xu; Jianyun Chen; Yin Wang; Yongqian Qu; Bo Liu; Yue Fang (Engineering Structures, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

A comprehensive analysis method for adverse geology in tunnels based on geological information and multi-source geophysical data - Peng Wang; Shi-shu Zhang; Wei-dong Chen; Yi-guo Xue; Zi-ming Qu; Hua-bo Xiao; Mao-xin Su; Kai Zhang (Applied Geophysics, 2025)

Integrated omics analysis reveals the effect of feeding scarcity on the lipid metabolism and apoptosis in Nibea coibor - Zhaoqiu Qu; Biao Yuan; Ruojing Li; Xubing Ba; Zhenjun Zhuang; Xin Yi; Jiayu Zhou; Qianwen Min; Zhongdian Dong; Na Zhao; Bo Zhang (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Research on hydraulic fracture propagation and interwell interference mechanisms during multi-well pad fracturing in shale reservoirs - Bo Zhang; Tiankui Guo; Ming Chen; Linrui Xue; Yunpeng Wang; Haiyang Wang; Jiwei Wang; Zhanqing Qu; Wentao Ma (Engineering Geology, 2025)

Advanced fabrication of three-dimensional bicontinuous MXene/agarose composite monoliths for high-selective rapid separation of antibodies - Xiang-Dong Xu; Jing Li; Jun-Qi Zhang; Yuan Peng; Chen-Mei Sun; Ru-Qi Liang; Jian-Bo Qu (Chemical Engineering Journal, 2025)

Proppant Transport Coupled with Propagation of Three-Dimensional Hydraulic-Natural Fractures - Yunpeng Wang; Ming Chen; Tiankui Guo; Zhanqing Qu; Bo Zhang; Mingkun Lv; Wenyu Wang (Rock Mechanics and Rock Engineering, 2025)

Construction of a high-resolution city-level emission inventory based on multiple methods: a case study of Cangzhou City, China - Xin Bo; Wanyue Shan; Jiabao Qu; Tuantuan Lei; Minjie Sang; Zhaoling Li; Aijun Lin (Environment, Development and Sustainability, 2025)

Bioenhanced remediation of dibutyl phthalate contaminated black soil by immobilized biochar microbiota - Yue Tao; Yao Wang; Yunhe Cui; Rui Sun; Bo Zhang; Jianhua Qu; Hongguang Cai; Ying Zhang (Journal of Environmental Management, 2025)

Dietary nucleotides drive changes in infant fecal microbiota in vitro and gut microbiota-gut-brain development in neonatal rats: A potential “nitrogen source” for early microbiota growth - Zhihao Qu; Bo Zhang; Guopeng Lin; Min Guo; Peijun Tian; Linlin Wang; Wei Chen; Heng Zhang; Gang Wang (Food Chemistry, 2025)

Difunctional MOF-EDTA modified wood membrane for efficient water purification - Bo Yue; Zhongwei Pang; Yang Yu; Jianfei Wu; Jiafu Qu; Jundie Hu; Dan Tian; Jianzhang Li; Yahui Cai (Chemical Engineering Journal, 2025)

Research on the Influence of Shallow Buried Tunnel Crossing on the Stability of Overlying Frame Structure Building - Bo Wang; Suizi Jia; Mingyi Han; Jingkai Qu; Huimin Gong; Chao Lu; Ziming Qu (Journal of Marine Science and Engineering, 2024)
The land section of the Huangdao end of the Jiaozhou Bay Second Submarine Tunnel is extensively underlain by the Quaternary Loose Accumulation Layer. The tunnel passes through a weathered granite fracture zone with well-developed rock joints beneath the buildings. The tunnel excavation process significantly disturbs the buildings above, making them prone to settlement, cracking, and tilting. This research conducts numerical simulations of three tunnel excavation methods, and based on the results, compares the deformation behaviors of the ground surface and buildings under various conditions. The findings show that the double side-wall guide pit method has better adaptability in controlling surface settlement and building deformation than the vertical or curved CD method. Moreover, the removal of temporary supports significantly affects building settlement and tilt; this risk can be effectively reduced by controlling the stress relief ratio during the removal phase of the temporary supports in the tunnel. The significance of the study lies in the fact that by choosing an appropriate tunnel excavation support scheme, the disturbance impact on the overlying buildings can be minimized, and the construction safety and stability of the surrounding buildings can be guaranteed. The results of this study can provide initial guidance for constructing shallow-buried tunnels beneath existing buildings.

Oleanolic acid promotes porcine oocyte maturation by activating the Nrf2/HO-1 signalling pathway - Yan-Qiu Wang; Yan-Wei Dong; He-Xuan Qu; Jia-Jia Qi; Chen-Xuan Yan; Hua-Kai Wei; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

Spatio-temporal evolution and adaptive cycle of marine economy resilience in Bohai Rim Region - Jinghui Wu; Bo Li; Lixiao Zhang; Yi Qu (Regional Studies in Marine Science, 2024)

Evolution mechanism and improvement path of marine economy resilience in Bohai Rim Region - Jinghui Wu; Bo Li; Lixiao Zhang; Yi Qu (Regional Studies in Marine Science, 2024)

Development and optimization of an artificial neural network (ANN) model for predicting the cadmium fixation efficiency of biochar in soil - Yifan Wang; Liang Xu; Jianen Li; Yan Li; Yutong Zhou; Wei Liu; Yunhe Ai; Bo Zhang; Jianhua Qu; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Effective removal of Cr(VI) from water by ball milling sulfur-modified micron zero-valent iron：Influencing factors and removal mechanism - Jianhua Qu; Huiyao Li; Ziwei Li; Wei Peng; Bo Wang; Huiru Wang; Guangshan Zhang; Qi Hu; Lei Wang; Ying Zhang (Environmental Research, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Numerical investigation of flow around the sagging pipeline above an equilibrium scoured bed - Bo Yang; Bingchen Liang; Qin Zhang; Ming Zhao; Mengxiang Qu (Ocean Engineering, 2024)

Harnessing microbial biofilms in soil ecosystems: Enhancing nutrient cycling, stress resilience, and sustainable agriculture - Bo Zhang; Xiaoying Hu; Donglin Zhao; Yuping Wang; Jianhua Qu; Yue Tao; Zhonghui Kang; Hongqi Yu; Jingyi Zhang; Ying Zhang (Journal of Environmental Management, 2024)

Numerical simulation on multi-well fracturing considering multiple thin layers in vertical direction - Yunpeng Wang; Tiankui Guo; Ming Chen; Xuliang Jia; Dingwei Weng; Zhanqing Qu; Zunpeng Hu; Bo Zhang; Jiwei Wang (International Journal of Rock Mechanics and Mining Sciences, 2024)

Blood mercury mediates the associations between fish consumption and serum uric acid levels among Chinese adults: A nationally representative study - Changzi Wu; Bing Wu; Yingli Qu; Hui Fu; Yue Chen; Yifu Lu; Saisai Ji; Liang Ding; Zheng Li; Qi Sun; Miao Zhang; Xu Zhang; et al. (Environmental Research, 2024)

Effect of bedding planes and property contrast between layers on the propagation mechanism of hydraulic fracture height in shale reservoirs - Bo Zhang; Tiankui Guo; Ming Chen; Jiwei Wang; Jinhao Cao; Haiyang Wang; Zhanqing Qu (Computers and Geotechnics, 2024)

Improving carrier transport for stable and efficient perovskite solar cells via MXene-modified 2D perovskite capping layer - Yaobin Li; Yu Zou; Shuang Yang; Hantao Wang; Wenjin Yu; Haoqing Guo; Xiangdong Li; Yunxuan Cao; Yueli Liu; Zhenyu Tang; Bo Qu; Lixin Xiao; et al. (Chemical Engineering Journal, 2024)

Bioenergetic-active photoluminescent bioactive Nanodressing for proangiogenic MRSA infected wound repair and microenviroment monitoring - Liuyang Zhang; Chaoyan Hu; Yanzi Zhao; Sihua Li; Qian Huang; Long Zhang; Xiaoyan Qu; Bo Lei (Chemical Engineering Journal, 2024)

Controlled assembly and synthesis of oxygen-deficient W18O49 films based on solvent molecular strategy for electrochromic energy storage smart windows - Xiaohui Sun; Wei Wu; Nana Liu; Peng Li; Xueying Zhao; Zhaozhu Qu; Kunming Zhao; Bo Wang; Xianhui Rong; Xuyang Zhang; Guohua Wu; Xiangwei Wang (Chemical Engineering Journal, 2024)

Engineering multifunctional intracellular energy metabolism enhanced polycitrate-based hydrogel for MRSA infected wound therapy - Sihua Li; Yanzi Zhao; Meng Luo; Qingsong Zhang; Chaoyan Hu; Weipeng Qiang; Xiaoyan Qu; Qian Huang; Bo Lei (Chemical Engineering Journal, 2024)

Synthesis of magnetic chitosan-composite biochar and its removal of copper ions (Cu2+) and methylene blue (MB) dye from aqueous solutions - Yifan Wang; Liang Xu; Jianen Li; Zheyi Ren; Wei Liu; Yunhe Ai; Kaixiang Yang; Jianhua Qu; Bo Zhang; Ying Zhang (Environmental Science and Pollution Research, 2024)

Covalent immobilization of lipase on moderately hydrophilic gigaporous polystyrene microspheres for efficient biosynthesis of benzyl cinnamate - Jing Li; Xiang-Dong Xu; Jian Zhang; Xin-Yi Sui; Jian-Bo Qu (Journal of Environmental Chemical Engineering, 2024)

Research advances in detection of food adulteration and application of MALDI-TOF MS: A review - Danliangmin Song; Kai Dong; Shiyu Liu; Shiqian Fu; Feng Zhao; Chaoxin Man; Yujun Jiang; Kuangyu Zhao; Bo Qu; Xinyan Yang (Food Chemistry, 2024)

NH3/C2H6 and NH3/C2H5OH oxidation in a shock tube: Multi-speciation measurement, uncertainty analysis, and kinetic modeling - Mengdi Li; Denghao Zhu; Henrique Karas; Sumit Agarwal; Zhechao Qu; Kai Moshammer; Ravi Fernandes; Bo Shu (Chemical Engineering Journal, 2024)

Correction: Root Disturbance Effects of Four Halophytes on Soil Physiochemical Characteristics in Intertidal Ecotone of the Yellow River Estuary - Debin Sun; Di Zhou; Bo Guan; Yunzhao Li; Junbao Yu; Fanzhu Qu; Jisong Yang; Xuehong Wang; Xue Li (Wetlands, 2024)

The influence of chlorination additives on metal separation during the pyrometallurgical recovery of spent lithium-ion batteries - Guorui Qu; Yonggang Wei; Bo Li; Hua Wang (Waste Management, 2024)

Effective amendment of cadmium in water and soil before and after aging of nitrogen-doped biochar: Preparation optimization, removal efficiency and mechanism - Yifan Wang; Jianen Li; Qiaona Li; Liang Xu; Yunhe Ai; Wei Liu; Yutong Zhou; Boyu Zhang; Nan Guo; Bo Cao; Jianhua Qu; Ying Zhang (Journal of Hazardous Materials, 2024)

Theoretical investigation of threshold pressure gradient in hydrate-bearing clayey-silty sediments under combined stress and local thermal stimulation conditions - Jiangtao Qu; Gang Lei; Tianle Liu; Jiaxin Sun; Shaojun Zheng; Bo Qu (Gas Science and Engineering, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Liriodendrin stimulates proliferation and milk protein synthesis of mammary epithelial cells via the PI3K-DDX18 signaling - Youwen Qiu; Mingming Fu; Minghui Zhang; Bo Qu; Zhen Zhen (In Vitro Cellular & Developmental Biology - Animal, 2024)

New geographical records and molecular investigation of the ciliate Spirostomum - Sheng-Bo Zhou; Zhi-Yu Zhao; Ping Guan; Bo Qu (Protist, 2024)

Numerical simulation of fracture propagation morphology in hydraulic fracturing development of geothermal reservoirs based on the CDEM-THM3D - Wang Jiwei; Guo Tiankui; Chen Ming; Qu Zhanqing; Zhang Bo; Zhang Wei; Zhai Cheng; Zheng Peng (Computers and Geotechnics, 2024)

“Root Disturbance Effects of Four Halophytes on Soil Physiochemical Characteristics in Intertidal Ecotone of the Yellow River Estuary” - Debin Sun; Di Zhou; Bo Guan; Yunzhao Li; Junbao Yu; Fanzhu Qu; Jisong Yang; Xuehong Wang; Xue Li (Wetlands, 2024)

Dissecting the Implications of Calumenin in Malignancy and Heterogeneity of the Microenvironment of Clear Cell Renal Cell Carcinoma Using Multi-Omics Data - Xin-Qiang Wu; Zhi Shang; Cui Xiong; Wen-Hao Xu; Bo Dai; Yu-Ling Chen; Yu-Yang Feng; Yue Wang; Jia-Qi Su; Jian-Yuan Zhao; Hai-Liang Zhang; Yan Shi; et al. (Phenomics, 2024)

Impact of the COVID-19 pandemic on daily travel: Findings from New South Wales, Australia - Bo Du; Cheng Zhang; Tianyang Qu; Qi Wang; Quan Spring Zhou; Tingru Cui; Pascal Perez; Thomas Astell-Burt (Travel Behaviour and Society, 2024)

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Effect of initial moisture content, resulting from different ratios of vegetable waste to maize straw, on compost was mediated by composting temperatures and microbial communities at low temperatures - Shanshan Sun; Cheng Guo; Jianyu Wang; Li Ren; Jianping Qu; Qi Guan; Nongxiao Dou; Jiahui Zhang; Qiuhua Chen; Qi Wang; Jiguang Wang; Jieming Li; et al. (Chemosphere, 2024)

Different oxygen affinities of methanotrophs and Comammox Nitrospira inform an electrically induced symbiosis for nitrogen loss - Hao Wu; Wen-Bo Nie; Xin Tan; Guo-Jun Xie; Han Qu; Xin Zhang; Zhihao Xian; Jingyi Dai; Chun Yang; Yi Chen (Water Research, 2024)

Investigation of surrounding rock stability during proximal coal seams mining process and feasibility of ground control technology - Jinsong Fan; Qiang Yuan; Jie Chen; Yiwei Ren; Dingding Zhang; Hai Yao; Bo Hu; Yinghao Qu (Process Safety and Environmental Protection, 2024)

Influence of mixing uniformity between stabilisation materials and contaminated soil on the stabilisation efficiency of heavy metals - Yunlong Zhang; Lixia Sun; Bo Wu; Meng Zhang; Shuhai Guo; Linlin Li; Shuqi Li; Longlong Qu (Journal of Environmental Chemical Engineering, 2024)

Dextral shear initiation of the Kangguer Shear Zone in the East Tianshan: Constraints from a “porphyroclast” system - Bo Liu; Zhengle Chen; Mengmeng Qu; Feng Yuan; Awei Mabi; Mingqiang Sheng; Jing Liu; Fengbin Han; Wengao Zhang; Hailong Huo (Journal of Asian Earth Sciences, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Pollution characteristics, source apportionment, and health risk assessment of PM10 and PM2.5 in rooftop and kerbside environment of Lanzhou, NW China - Chen-ming Gu; Bo Wang; Qu Chen; Xiao-han Sun; Mei Zhang (Environmental Science and Pollution Research, 2024)

Investigation on high temperature point detection of spontaneous combustion of loose coal based on optimal acoustic signal - Jun Deng; Gaoyang Qu; Shuaijing Ren; Caiping Wang; Yang Xiao; Jinrui Wang; Bo Sa; Xiadan Duan; Nannan Yang; Xiaqi Zhao (Process Safety and Environmental Protection, 2024)

Degradation and enhanced oil recovery potential of Alcanivorax borkumensis through production of bio-enzyme and bio-surfactant - Shuyuan Deng; Bo Wang; Hong Zhang; Ruixue Qu; Shanshan Sun; Qing You; Yuehui She; Fan Zhang (Bioresource Technology, 2024)

Hypothetical protein MAA_07646 is required for stress resistance and pathogenicity in Metarhizium robertsii - MingYue Chen; YaShuai Yu; YouMin Tong; Hao Wu; JiaoJiao Qu; Yang Yang; Bo Huang (World Journal of Microbiology and Biotechnology, 2024)

Defining the land use area threshold and optimizing its structure to improve supply-demand balance state of ecosystem services - Pei Huang; Xiaoqing Zhao; Junwei Pu; Zexian Gu; Yuju Ran; Yifei Xu; Beihao Wu; Wenwen Dong; Guoxun Qu; Bo Xiong; Longjin Zhou (Journal of Geographical Sciences, 2024)

Xenocrystic zircons from mafic volcanic rocks in the Bikou Terrane: A window to trace the Paleoarchean to Mesoproterozoic crustal evolution of the northwestern Yangtze Block, South China - Bo Hui; Yunpeng Dong; Hongjun Qu; Shengsi Sun; Franz Neubauer; Feifei Zhang; Rutao Zang; Shuxuan Yan; Guiyun Wang (Precambrian Research, 2024)

A comprehensive assessment indicator of the water-energy-food nexus system based on the material consumption relationship - Lingang Hao; Jingjie Yu; Ping Wang; Chunhui Han; Boris Gojenko; Bo Qu; Enhui Jiang; Sherzod Muminov (Journal of Hydrology, 2024)

Functional analyses of TRAF6 gene in Argopecten scallops - Xiaotong Zhang; Xia Wang; Jieyu Chen; Min Chen; Xia Lu; Junhao Ning; Haijun Liu; Guilong Liu; Xin Xu; Xiaoxu Qu; Kai Yu; He Xu; et al. (Fish & Shellfish Immunology, 2024)

Research on fracture propagation of hydraulic fracturing in a fractured shale reservoir using a novel CDEM-based coupled HM model - Bo Zhang; Tiankui Guo; Ming Chen; Jiwei Wang; Zhanqing Qu; Haiyang Wang; Heng Zheng; Wuguang Li (Computers and Geotechnics, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Uptake and accumulation of di(2-ethylhexyl) phthalate (DEHP) in a soil-ginseng system and toxicological mechanisms on ginseng (Panax ginseng C.A. Meyer) - Yu-shun Lu; Zheng-bo Liu; Yan-yang Xu; Ji-yue Sha; Di Qu; Yin-shi Sun (Science of The Total Environment, 2024)

Biodegradation of atrazine with biochar-mediated functional bacterial biofilm: Construction, characterization and mechanisms - Bo Zhang; Jingdan Zhang; Yuping Wang; Jianhua Qu; Zhao Jiang; Xu Zhang; Yue Tao; Yifan Wang; Zhonghui Kang; Songting Han; Jingyi Zhang; Ying Zhang (Journal of Hazardous Materials, 2024)

Porous hydrochar loaded nZVI as an efficient catalyst to activate persulfate for phenol degradation: Performance and mechanism - Bo Cao; Jianhua Qu; Wenhui Bian; Qiqi Hu; Xinyan Fu; Guangshan Zhang; Yuezhi Zhang; Yue Tao; Zhao Jiang; Ying Zhang (Journal of Cleaner Production, 2024)

A novel sample pretreatment of nanofiber-packed solid-phase extraction of aflatoxin B1, B2, G1 and G2 in foods and simultaneous determination with HPLC - Yunzheng Wang; Lanling Chu; Jiansong Qu; Bo Ding; Xuejun Kang (Food Chemistry, 2024)

Enhanced Removal of Sulfonated Lignite from Oilfield Wastewater by Soft Colloidal Templated Porous Structure of MgAl-LDH - Ying Tang; Bingbing Bai; Ya Wu; Bo Yang; Ling Zhou; Chentun Qu (Water, Air, & Soil Pollution, 2024)

Adsorption performance and mechanism of TiO2/PVDF-based lithium-ion imprinted membrane in leaching solution of spent lithium-ion batteries - Guorui Qu; Jiaqi Yang; Yuxuan Ran; Bo Li; Hua Wang; Yonggang Wei (Journal of Cleaner Production, 2024)

Magnetic characteristics of atmospheric particulate matter and its indication of atmospheric pollution during winter in Lanzhou, NW China - Bo Wang; Chen-ming Gu; Qu Chen; Mei Zhang; Xiao-han Sun; Jia Jia (Atmospheric Environment, 2024)

Rare earth element behaviors of groundwater in overlying aquifers under the influence of coal mining in northern Ordos Basin, China - Fengxia Liu; Guangcai Wang; Bo Li; Chenyu Wang; Shen Qu; Fu Liao (Environmental Science and Pollution Research, 2024)

Inhibition of FSP1 impairs early embryo developmental competence in pigs - Yan-Qiu Wang; He-Xuan Qu; Yan-Wei Dong; Jia-Jia Qi; Hua-Kai Wei; Hao Sun; Hao Jiang; Jia-Bao Zhang; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

Urbanization reduces fish taxonomic and functional diversity while increases phylogenetic diversity in subtropical rivers - Bo Yang; Xiao Qu; Han Liu; Min Yang; Wei Xin; Weiming Wang; Yushun Chen (Science of The Total Environment, 2024)

Efficient separation and extraction of lithium from low-grade claystone by chloride salt-enhanced roasting process - Yuxuan Ran; Guorui Qu; Jiaqi Yang; Shiwei Zhou; Bo Li; Hua Wang; Yonggang Wei (Journal of Cleaner Production, 2024)

Mechanism for metal loss in smelting of recycled spent lithium-ion batteries: The overlooked role of refractory materials - Guorui Qu; Jiaqi Yang; Yonggang Wei; Shiwei Zhou; Bo Li; Hua Wang (Journal of Environmental Management, 2024)

Retraction Note to: Mesothelial cells differentiate into fibroblast-like cells under the scirrhous gastric cancer microenvironment and promote peritoneal carcinomatosis in vitro and in vivo - Zhi-Dong Lv; Hai-Bo Wang; Qian Dong; Bin Kong; Jian-guo Li; Zhao-Chuan Yang; Hui-Li Qu; Wei-Hong Cao; Hui-Mian Xu (Molecular and Cellular Biochemistry, 2024)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Analysis of Seasonal Differences of Chlorophyll, Dimethylsulfide, and Ice Between the Greenland Sea and the Barents Sea - Guangsheng Zhong; Bo Qu (Journal of Ocean University of China, 2023)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Synergistic mechanism of formaldehyde adsorption by intrinsic defects and carboxyl groups on the surface of carbon materials - Zekun Sun; Zhonghua Wang; Xue Yang; Kaibo An; Zhibin Qu; Ziyu Tang; Shiwei Lai; Mingqi He; Lei Yang; Bo Zhou; Haiqian Zhao (Chemosphere, 2023)

Reproducible Abnormalities and Diagnostic Generalizability of White Matter in Alzheimer’s Disease - Yida Qu; Pan Wang; Hongxiang Yao; Dawei Wang; Chengyuan Song; Hongwei Yang; Zengqiang Zhang; Pindong Chen; Xiaopeng Kang; Kai Du; Lingzhong Fan; Bo Zhou; et al. (Neuroscience Bulletin, 2023)

A strain of Vibrio alginolyticus isolated from Azumapecten farreri and its pathogenic mechanism using CRISPR-Cas9 technology - Jingxue Ma; Peiyu Zhang; Minggang Zheng; Bo Wang; Ping Gao; Lingyun Qu; Fengrong Zheng (Biotechnology Letters, 2023)

S-doped core–shell heterojunction Fenton catalyst (Fe3O4-S@PVP@UIO-66-(SH)2) for enhanced activation of hydroxyl radicals: Synergistic enrichment and degradation mechanism - Dingtang Li; Wei Qu; Bo Han; Jun Gao; Shuyu Xie; Dongmei Chen (Chemical Engineering Journal, 2023)

The induction of ferroptosis by KLF11/NCOA4 axis: the inhibitory role in clear cell renal cell carcinoma - Zi-Qi Zhou; Xi Lv; Shi-Bo Liu; Hong-Chen Qu; Qing-Peng Xie; Long-Feng Sun; Gang Li (Human Cell, 2023)

A quantity-distribution synthesized framework for risk assessment of algal blooms - Ting Zhou; Hongwei Qu; Yan Wang; Juha M. Alatalo; Jun Qian; Sunxinyu Zhuan; Bo Jiang (Journal of Hydrology, 2023)

Applicability of the reduction smelting recycling process to different types of spent lithium-ion batteries cathode materials - Guorui Qu; Jiaqi Yang; Hao Wang; Yuxuan Ran; Bo Li; Yonggang Wei (Waste Management, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Nitrogen deposition further increases Ambrosia trifida root exudate invasiveness under global warming - Ke Xu; Xinyue Liu; Changxin Zhao; Qingmin Pan; Xiaoxing Chen; Ning Jiang; Cuiping Du; Yufeng Xu; Meini Shao; Bo Qu (Environmental Monitoring and Assessment, 2023)
Invasive plants can change the soil ecological environment in the invasion area to adapt to their growth and reproduction through root exudates. Root exudates are the most direct manifestation of plant responses to external environmental changes, but there is a lack of studies on root exudates of invasive plants in the context of inevitable global warming and nitrogen deposition. In this research, we used widely targeted metabolomics to investigate Ambrosia trifida root exudates during seedling and maturity under warming and nitrogen deposition to reveal the possible mechanisms of A. trifida adaptation to climate change. The results showed that the organic acids increased under warming condition but decreased after nitrogen addition in the seedling stage. Phenolic acids increased greatly after nitrogen addition in the mature stage. Most phenolic acids were annotated in the phenylpropane metabolic pathway and tyrosine metabolism. Therefore, nitrogen deposition may increase the adaptability of A. trifida through root exudates, making it more invasive under global warming. The results provide new ideas for preventing and controlling the invasion of A. trifida under climate change.

One-step self-assembly of Fe-biochar composite for enhanced persulfate activation to phenol degradation: Different active sites-induced radical/non-radical mechanism - Bo Cao; Jianhua Qu; Yingyu Chu; Yujiao Zhu; Yuxin Jiang; Xiubo Zhang; Mingze Sun; Zhao Jiang; Shouyi Ma; Ying Zhang (Chemosphere, 2023)

Outdoor thermal comfort in urban and rural open spaces: A comparative study in China's cold region - Tingting Yuan; Bo Hong; Hongyun Qu; Aowei Liu; Yuange Zheng (Urban Climate, 2023)

Cyclic pentapeptides with anti-inflammatory, cytotoxic or α-glucosidase inhibitory activities from Basidiobolus meristosporus - Cheng Zhao; Jiaojiao Qu; Ruili Lu; Renjie Chen; Quheng Dong; Bo Huang; Guanhu Bao; Fenglin Hu (Phytochemistry, 2023)

Chlorination mechanism and kinetics of cathode materials for spent LiCoO2 batteries in the presence of graphite - Guorui Qu; Yonggang Wei; Bo Li; Hua Wang (Journal of Environmental Chemical Engineering, 2023)

Potential roles of IFI44 genes in high resistance to Vibrio in hybrids of Argopecten scallops - Xiaoxu Qu; Xia Wang; Bo Liu; Min Chen; Junhao Ning; Haijun Liu; Guilong Liu; Xin Xu; Xiaotong Zhang; Kai Yu; He Xu; Xia Lu; et al. (Fish & Shellfish Immunology, 2023)

Characterization of TRAF genes and their responses to Vibrio anguillarum challenge in Argopecten scallops - Xia Wang; Xiaoxu Qu; Xia Lu; Min Chen; Junhao Ning; Haijun Liu; Guilong Liu; Xin Xu; Xiaotong Zhang; Kai Yu; He Xu; Bo Liu; et al. (Fish & Shellfish Immunology, 2023)

Formulation improvement of a concentrated enzyme detergent for high-speed rail trains through life cycle assessment methodology - Changyan Yang; Yu Gong; Yinhang Qu; Jiayi Li; Bohan Yang; Rui Li; Dorothy S. Zhang; Baowei Wang; Yigang Ding; Bo Zhang (Environment, Development and Sustainability, 2023)

Explicit and size-adaptive PSO-based feature selection for classification - Litao Qu; Weibin He; Jianfei Li; Hua Zhang; Cheng Yang; Bo Xie (Swarm and Evolutionary Computation, 2023)

Biomimetic cellulose-nanocrystalline-based composite membrane with high flux for efficient purification of oil-in-water emulsions - Jianfei Wu; Ziwei Cui; Yuxuan Su; Yang Yu; Bo Yue; Jundie Hu; Jiafu Qu; Dan Tian; Xianxu Zhan; Jianzhang Li; Yahui Cai (Journal of Hazardous Materials, 2023)

Effects of thermal-olfactory interactions on emotional changes in urban outdoor environments - Jiayu Chang; Meng Du; Bo Hong; Hongyun Qu; Huiying Chen (Building and Environment, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Noval bio-organic fertilizer containing Arthrobacter sp. DNS10 alleviates atrazine-induced growth inhibition on soybean by improving atrazine removal and nitrogen accumulation - Zhao Jiang; Qi Shao; Yu Li; Bo Cao; Jin Li; Zheyi Ren; Jianhua Qu; Ying Zhang (Chemosphere, 2023)

Analysis of lunar wrinkle ridges regarding the maximum displacement–length scaling relationship and relevant geological factors - Chenfan Li; Bo Li; Xiaohui Fu; Le Qiao; Zongcheng Ling; Jianguo Yan; Shaojie Qu; Shengbo Chen (Icarus, 2023)

Mechanisms of synergistic inhibition of NaCl and glycine mixtures on methane hydrate formation: Experimental and molecular dynamic simulation - Jianlong Wang; Jinsheng Sun; Ren Wang; Rongchao Cheng; Bo Liao; Yuanzhi Qu; Qibing Wang; Jintang Wang; Kaihe Lv (Gas Science and Engineering, 2023)

Air pollutant emissions and reduction potentials from municipal solid waste incineration in China - Ling Tang; Jing Guo; Ruxing Wan; Min Jia; Jiabao Qu; Ling Li; Xin Bo (Environmental Pollution, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Corrigendum to “Grafting with an invasive Xanthium strumarium improves tolerance and phytoremediation of native congener X. sibiricum to cadmium/copper/nickel tailings” [Chemosphere, 308 (2022) 136561] - Chenyang Xue; Lizong Sun; Bo Qu; Yingmei Gao; Zhi Liu; Cheng Guo; Wanbin Liu; Wenyue Chang; Peidong Tai (Chemosphere, 2023)

High-efficiency decontamination of Pb(II) and tetracycline in contaminated water using ball-milled magnetic bone derived biochar - Jianhua Qu; Bo Zhang; Hua Tong; Yang Liu; Siqi Wang; Shuqi Wei; Lei Wang; Yifan Wang; Ying Zhang (Journal of Cleaner Production, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Surface adsorption guided design of semicrystalline nickel-iron hydroxide for highly-sensitive glucose sensing - Minyuan Tan; Ming Ni; Xinyu Liu; Bo Qu; Xi Lin; Daochuan Jiang; Yupeng Yuan; Haiwei Du (Chemical Engineering Journal, 2023)

A novel approach for the recovery and cyclic utilization of valuable metals by co-smelting spent lithium-ion batteries with copper slag - Guorui Qu; Bo Li; Yonggang Wei (Chemical Engineering Journal, 2023)

Microscopic molecular insights into methane hydrate growth on the surfaces of clay minerals: Experiments and molecular dynamics simulations - Ren Wang; Bo Liao; Jintang Wang; Jinsheng Sun; Yudou Wang; Jianlong Wang; Qibing Wang; Yuanzhi Qu; Rongchao Cheng (Chemical Engineering Journal, 2023)

Local and Global Abnormalities in Pre-symptomatic Huntington’s Disease Revealed by 7T Resting-state Functional MRI - Juan-Juan Xie; Xiao-Yan Li; Yi Dong; Cong Chen; Bo-Yi Qu; Shuang Wang; Han Xu; Anna Wang Roe; Hsin-Yi Lai; Zhi-Ying Wu (Neuroscience Bulletin, 2023)

Hydrothermal carbonization of alfalfa: role of processing variables on hydrochar properties - Jun Zhou; Mingjie Yu; Jianhua Qu; Modupe Sarah Akindolie; Fuxuan Bi; Yang Liu; Zhao Jiang; Lei Wang; Bo Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Vertical Chlorophyll and Dimethylsulfide Profile Simulations in Southern Greenland Sea - Bo Qu; Wenjing Sun (Journal of Ocean University of China, 2022)

Mitigation of atrazine-induced oxidative stress on soybean seedlings after co-inoculation with atrazine-degrading bacterium Arthrobacter sp. DNS10 and inorganic phosphorus-solubilizing bacterium Enterobacter sp. P1 - Zhao Jiang; Qi Shao; Yuxin Chu; Ning An; Bo Cao; Zheyi Ren; Jin Li; Jianhua Qu; Maofeng Dong; Ying Zhang (Environmental Science and Pollution Research, 2022)

Effects of different water conditions on the cadmium hyperaccumulation efficiency of Rorippa sylvestris (L.) Besser and Rorippa amphibia Besser - Bo Qu; Yunning Yuan; Linyu Wang; Yinuo Liu; Xuhui Chen; Meini Shao; Yufeng Xu (Environmental Science and Pollution Research, 2022)

Control, Treatment and Restoration of Contaminated Soils - Hong-Bo Li; Changsheng Qu; Xinyi Cui; Yang Song; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2022)

Mechanical failure analysis during direct shear of double-joint rock mass - Feng Jiang; Gang Wang; Peng He; Bin Hou; Shu-bo Zhang; Shang-qu Sun; Cheng-cheng Zheng; Yue Wu (Bulletin of Engineering Geology and the Environment, 2022)

Variation of the floral traits and sexual allocation patterns of Clematis tangutica to the altitudinal gradient of the eastern Qinghai- Tibet Plateau - Xiang Zhao; Qinzheng Hou; Xue Su; Bo Qu; Baoli Fan; Hui Zhang; Kun Sun (Biologia, 2022)

Assessing the sustainable safety practices based on human behavior factors: an application to Chinese petrochemical industry - Junqiao Zhang; Qiang Qu; Xue-bo Chen (Environmental Science and Pollution Research, 2022)

Recent Trends in Satellite-Derived Chlorophyll and Aerosol Optical Depth Together with Simulated Dimethylsulfide in the Eastern China Marginal Seas - Bo Qu; Albert J. Gabric (Journal of Ocean University of China, 2022)

Attention Field Size Alters Patterns of Population Receptive Fields in the Early Visual Cortex - Bo Liu; Xiaochun Wang; Le Wang; Qiaojun Qu; Wei Zhang; Bin Wang; Jie Xiang; Ting Yan; Tianyi Yan; Hui Zhang (Neuroscience Bulletin, 2022)

Critical Risk Indicators (CRIs) for the electric power grid: a survey and discussion of interconnected effects - Judy P. Che-Castaldo; Rémi Cousin; Stefani Daryanto; Grace Deng; Mei-Ling E. Feng; Rajesh K. Gupta; Dezhi Hong; Ryan M. McGranaghan; Olukunle O. Owolabi; Tianyi Qu; Wei Ren; Toryn L. J. Schafer; et al. (Environment Systems and Decisions, 2021)

Characteristics and Environmental Response of White Secondary Mineral Precipitate in the Acid Mine Drainage From Jinduicheng Mine, Shaanxi, China - Cong Lu; Bo Yang; Xing Cui; Sichang Wang; Chengtun Qu; Weiwei Zhang; Bo Zhou (Bulletin of Environmental Contamination and Toxicology, 2021)

Decontamination of DNA in Taq DNA polymerase reagents using nylon membranes for monitoring of GMOs - Shi Rong Zhao; Bo Qu; Jae Kwang Kim; Bumkyu Lee (Plant Biotechnology Reports, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Wnt8a is one of the candidate genes that play essential roles in the elongation of the seahorse prehensile tail - Bo Zhang; Geng Qin; Lili Qu; Yanhong Zhang; Chunyan Li; Chunlei Cang; Qiang Lin (Marine Life Science & Technology, 2021)

Integrative analysis of prognostic long non-coding RNAs with copy number variation in bladder cancer - Wenwen Zhong; Dejuan Wang; Bing Yao; Xiaoxia Chen; Zhongyang Wang; Hu Qu; Bo Ma; Lei Ye; Jianguang Qiu (Journal of Zhejiang University-SCIENCE B, 2021)

Molecular characterization of a novel totivirus infecting the basal fungus Conidiobolus heterosporus - Jiaojiao Qu; Najie Shi; Guogen Yang; Bo Huang (Archives of Virology, 2021)

Analysis of Stratigraphic Subsidence Caused by Sand Leakage in Tunnel Lining - Zhongchang Wang; Tong Qu; Bo Li; Aoxiang Wang (Geotechnical and Geological Engineering, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

Morphological and anatomical characteristics of exserted stigma sterility and the location and function of SlLst (Solanum lycopersicum Long styles) gene in tomato - Mo-zhen Cheng; Chao Gong; Bo Zhang; Wei Qu; Hao-nan Qi; Xiu-ling Chen; Xing-yuan Wang; Yao Zhang; Jia-yin Liu; Xiao-dong Ding; You-wen Qiu; Ao-xue Wang (Theoretical and Applied Genetics, 2021)

Sigma-1 receptor ligands improves ventricular repolarization-related ion remodeling in rats with major depression disorder - Yan Guo; Cui Zhang; Xiuhuan Chen; Xin Liu; Tianxin Ye; Yuhong Fo; Shaobo Shi; Chuan Qu; Jinjun Liang; Bo Shen; Bo Yang (Psychopharmacology, 2021)

Study on Effects of Low Viscosity Fluid Pre-injection on Hydraulic Fracture Complexity in Tight Heterogeneous Glutenite Reservoirs - Liaoyuan Zhang; Zhanqing Qu; Mingyang Zhai; Aishan Li; Bo Huang; Zilin Zhang (Geotechnical and Geological Engineering, 2021)

Polycyclic polyprenylated acylphloroglucinols from Hypericum choisianum - Hai-Bo Zhang; Xu Zhang; Kun Jiang; Shi-Jin Qu; Ling-Hua Meng; Qun Lu; Chang-Heng Tan (Natural Product Research, 2021)

Bioactive tigliane diterpenoids from the latex of Euphorbia fischeriana - Yan-Yan Deng; Bo Qu; Zhong-Lang Zhan; An-Qi Wang; Wei Zhou; Ming-Yue Jia; Juan Hua; Shi-Hong Luo (Natural Product Research, 2021)

A rare mutant of OFD1 gene responsible for Joubert syndrome with significant phenotype variation - Yang-wei Zhang; Hai-bo Qu; Ning Long; Xiang-you Leng; Yun-qiang Liu; Yuan Yang (Molecular Genetics and Genomics, 2021)

Simulated perturbation in the sea-to-air flux of dimethylsulfide and the impact on polar climate - Bo Qu; Albert J. Gabric; Rebecca Jackson (Journal of Oceanology and Limnology, 2021)

A Comparison of the Development of Wetland Restoration Techniques in China and Other Nations - Di Zhou; Junbao Yu; Bo Guan; Yunzhao Li; Miao Yu; Fanzhu Qu; Chao Zhan; Zhenbo Lv; Huifeng Wu; Qing Wang; Jisong Yang (Wetlands, 2020)

Transcriptional profiling analysis of OsDT11-mediated ABA-dependent signal pathway for drought tolerance in rice - Man Zhao; Yanhu Ju; Bo Zhao; Xiaoming Li; LIli Dai; Jicheng Qu; Zhaohui Chu; Xinhua Ding (Plant Biotechnology Reports, 2020)

First record of field dodder (Cuscuta campestris) parasitizing invasive buffalobur (Solanum rostratum) - Wei-Bin Wang; Fan-Fan Gao; Mei-Ni Shao; Ming-Chao Liu; Hong-Feng Zhai; Bo Qu; Yu-Long Feng (Journal of Plant Pathology, 2020)

Elastic reverse-time migration in irregular tunnel environment based on polar coordinates - Ying-Ming Qu; Chang Zhou; Qurmet Worral; Zhen-Chun Li; Chang-Bo Wang; Jun-Zhi Sun (Applied Geophysics, 2020)

MiR-155 inhibition alleviates suppression of osteoblastic differentiation by high glucose and free fatty acids in human bone marrow stromal cells by upregulating SIRT1 - Bo Qu; Jun He; Zhimou Zeng; Hongsheng Yang; Zhanli Liu; Zongrui Cao; Hua Yu; Wen Zhao; Xianming Pan (Pflügers Archiv - European Journal of Physiology, 2020)

Establishment of geochemical baseline and multiple assessment of vanadium pollution in sediment cores from the two cascade reservoirs, North China - Jiankang Wang; Wenqi Peng; Shaoming Wang; Bo Gao; Xiaodong Qu; Min Zhang; Dongyu Xu (Environmental Science and Pollution Research, 2020)

Diversity Distributions and the Anthocyanin Associations of Fungal Endophytes in Different Colored Grapevine Leaves - Jing-Chao Chen; Man Yu; Fang Liu; Jin-Zhuo Qu; Xiao-Xia Pan; Han-Bo Zhang; Ming-Zhi Yang (Journal of Plant Biology, 2020)

Serious Selenium Deficiency in the Serum of Patients with Kashin–Beck Disease and the Effect of Nano-Selenium on Their Chondrocytes - Liyun Wang; Jiafeng Yin; Bo Yang; Chengjuan Qu; Jian Lei; Jing Han; Xiong Guo (Biological Trace Element Research, 2020)

Comparison Between Early and Late 21stC Phytoplankton Biomass and Dimethylsulfide Flux in the Subantarctic Southern Ocean - Bo Qu; Albert J. Gabric; Limei Jiang; Chunyue Li (Journal of Ocean University of China, 2020)

Genome-Wide Identification and Comparative Expression Profile Analysis of the Long-Chain Acyl-CoA synthetase (LACS) Gene Family in Two Different Oil Content Cultivars of Brassica napus - Zhongchun Xiao; Nannan Li; Shufeng Wang; Juanjuan Sun; Liyuan Zhang; Chao Zhang; Hong Yang; Huiyan Zhao; Bo Yang; Lijuan Wei; Hai Du; Cunmin Qu; et al. (Biochemical Genetics, 2019)

Mesorhizobium carbonis sp. nov., isolated from coal bed water - Jing Li; Wen Xin; Zhen-Zhen Xu; Fang-Qin Xiang; Jing-Jing Zhang; Li-Jun Xi; Jian-Bo Qu; Jian-Guo Liu (Antonie van Leeuwenhoek, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Comparative Transcriptome Analysis of Rhizoctonia solani-resistant and -Susceptible Rice Cultivars Reveals the Importance of Pathogen Recognition and Active Immune Responses in Host Resistance - Zhengjie Yuan; Yu Zhang; Guojuan Xu; Dongling Bi; Haiyan Qu; Xiaowei Zou; Xiaoqing Gao; Haihe Yang; Haiyan He; Xuli Wang; Jiandong Bao; Shimin Zuo; et al. (Journal of Plant Biology, 2018)

The relationships among aerosol optical depth, ice, phytoplankton and dimethylsulfide and the implication for future climate in the Greenland Sea - Bo Qu; Albert J. Gabric; Li Zhao; Wenjing Sun; Hehe Li; Peijuan Gu; Limei Jiang; Meifang Zeng (Acta Oceanologica Sinica, 2018)

Feature analysis and primary causes of pre-flood season “cumulative effect” of torrential rain over South China - Qu-cheng Chu; Qi-guang Wang; Shao-bo Qiao; Guo-lin Feng (Theoretical and Applied Climatology, 2018)

DEAD-box helicase 6 (DDX6) is a new negative regulator for milk synthesis and proliferation of bovine mammary epithelial cells - Zhen Zhen; Minghui Zhang; Xiaohan Yuan; Bo Qu; Yanbo Yu; Xuejun Gao; Youwen Qiu (In Vitro Cellular & Developmental Biology - Animal, 2018)

QTL mapping of domestication and diversifying selection related traits in round-fruited semi-wild Xishuangbanna cucumber (Cucumis sativus L. var. xishuangbannanesis) - Yupeng Pan; Shuping Qu; Kailiang Bo; Meiling Gao; Kristin R. Haider; Yiqun Weng (Theoretical and Applied Genetics, 2017)

Analysis of Dynamic Fracture Compliance Based on Poroelastic Theory. Part I: Model Formulation and Analytical Expressions - Ding Wang; Shou-Li Qu; Ping-Bo Ding; Qun Zhao (Pure and Applied Geophysics, 2017)

The ecological adaptability of Phragmites australis to interactive effects of water level and salt stress in the Yellow River Delta - Bo Guan; Junbao Yu; Aixin Hou; Guangxuan Han; Guangmei Wang; Fanzhu Qu; Jiangbao Xia; Xuehong Wang (Aquatic Ecology, 2017)

NFAT5 protects astrocytes against oxygen–glucose–serum deprivation/restoration damage via the SIRT1/Nrf2 pathway - Xun Xia; Bo Qu; Yun-Ming Li; Li-Bin Yang; Ke-Xia Fan; Hui Zheng; Hai-Dong Huang; Jian-Wen Gu; Yong-Qin Kuang; Yuan Ma (Journal of Molecular Neuroscience, 2017)

Causes and controlling pattern of sand hazards at the Danghe Reservoir of Dunhuang in Northwest China - Sheng-bo Xie; Jian-jun Qu; Ying-jun Pang (Journal of Mountain Science, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

Computational identification and characterization of novel microRNA in the mammary gland of dairy goat (Capra hircus) - BO QU; YOUWEN QIU; ZHEN ZHEN; FENG ZHAO; CHUNMEI WANG; YINGJUN CUI; QIZHANG LI; LI ZHANG (Journal of Genetics, 2016)

Chicken gga-miR-130a targets HOXA3 and MDFIC and inhibits Marek’s disease lymphoma cell proliferation and migration - Bo Han; Ling Lian; Xin Li; Chunfang Zhao; Lujiang Qu; Changjun Liu; Jiuzhou Song; Ning Yang (Molecular Biology Reports, 2016)

A green vendor-managed inventory analysis in supply chains under carbon emissions trading mechanism - Yushan Jiang; Bo Li; Xiaolong Qu; Yuepeng Cheng (Clean Technologies and Environmental Policy, 2016)

Structural controls on joint development in the southeastern margin of the Ordos basin - Linlin Wang; Bo Jiang; Jilin Wang; Zhenghui Qu; Run Chen (Arabian Journal of Geosciences, 2016)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Unambiguous combined correlation functions for sine-BOC signal tracking - Tao Yan; Jiaolong Wei; Zuping Tang; Bo Qu; Zhihui Zhou (GPS Solutions, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Molecular Interactions of Flavonoids to Hyaluronidase: Insights from Spectroscopic and Molecular Modeling Studies - Hua-jin Zeng; Jiao Ma; Ran Yang; You Jing; Ling-bo Qu (Journal of Fluorescence, 2015)

Effects of freeze-thaw cycles on soil mechanical and physical properties in the Qinghai-Tibet Plateau - Sheng-bo Xie; Qu Jian-jun; Lai Yuan-ming; Zhou Zhi-wei; Xu Xiang-tian (Journal of Mountain Science, 2015)

Structural control on pore-fracture characteristics of coals from Xinjing coal mine, northeastern Qinshui basin, China - Jiegang Liu; Bo Jiang; Ming Li; Zhenghui Qu; Linlin Wang; Lei Li (Arabian Journal of Geosciences, 2015)

Thyroid hormone responsive protein spot 14 enhances lipogenesis in bovine mammary epithelial cells - Yingjun Cui; Zhiyu Liu; Xia Sun; Xiaoming Hou; Bo Qu; Feng Zhao; Xuejun Gao; Zhe Sun; Qingzhang Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

A new ellagic acid derivative from Polygonum runcinatum - Zhi-Hong Zhou; Min-Zhuo Liu; Meng-Hua Wang; Wei Qu; Jian-Bo Sun; Jing-Yu Liang; Fei-Hua Wu (Natural Product Research, 2015)

Up-regulation of integrin α6β4 expression by mitogens involved in dairy cow mammary development - Feng Zhao; Chang Liu; Yu-Meng Hao; Bo Qu; Ying-Jun Cui; Na Zhang; Xue-Jun Gao; Qing-Zhang Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Genetic association study between INSULIN pathway related genes and high myopia in a Han Chinese population - Xiaoqi Liu; Pu Wang; Chao Qu; Hong Zheng; Bo Gong; Shi Ma; He Lin; Jing Cheng; Zhenglin Yang; Fang Lu; Yi Shi (Molecular Biology Reports, 2015)

A trehalose ester from Lancea tibetica - Shi-Jun Liu; Zhi-Xin Liao; Chao Liu; Yan-Bo Qu (Natural Product Research, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Functional analysis of FABP3 in the milk fat synthesis signaling pathway of dairy cow mammary epithelial cells - Meng-yao Liang; Xiao-ming Hou; Bo Qu; Na Zhang; Nan Li; Ying-jun Cui; Qing-zhang Li; Xue-jun Gao (In Vitro Cellular & Developmental Biology - Animal, 2014)

Heterochronic bilateral ectopic pregnancy after ovulation induction - Bo Zhu; Gu-feng Xu; Yi-feng Liu; Fan Qu; Wei-miao Yao; Yi-min Zhu; Hui-juan Gao; Dan Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Spectroscopy and Molecular Docking Study on the Interaction Behavior Between Nobiletin and Pepsin - Hua-jin Zeng; Tingting Qi; Ran Yang; Jing You; Ling-bo Qu (Journal of Fluorescence, 2014)

Controls on migration and aggregation for tectonically sensitive elements in tectonically deformed coal: An example from the Haizi mine, Huaibei coalfield, China - YunBo Li; Bo Jiang; ZhengHui Qu (Science China Earth Sciences, 2014)

Differential expression of the melanocortin-4 receptor in male and female C57BL/6J mice - HaiE Qu; JianPing Li; Wei Chen; YuMei Li; Qian Jiang; HuaiZhi Jiang; JinLong Huo; ZhiHui Zhao; Bo Liu; QiaoLing Zhang (Molecular Biology Reports, 2014)

A new taxane diterpenoid from Taxus chinensis var. mairei - Zhi-Hong Zhou; Wei Qu; Min-Zhuo Liu; Jian-Bo Sun; Meng-Hua Wang; Jing-Yu Liang; Fei-Hua Wu (Natural Product Research, 2014)

RETRACTED ARTICLE: Mesothelial cells differentiate into fibroblast-like cells under the scirrhous gastric cancer microenvironment and promote peritoneal carcinomatosis in vitro and in vivo - Zhi-Dong Lv; Hai-Bo Wang; Qian Dong; Bin Kong; Jian-guo Li; Zhao-Chuan Yang; Hui-Li Qu; Wei-Hong Cao; Hui-Mian Xu (Molecular and Cellular Biochemistry, 2013)

Conservation genetics of the endangered terrestrial orchid Liparis japonica in Northeast China based on AFLP markers - Xuhui Chen; Junjie Guan; Rui Ding; Qun Zhang; Xingze Ling; Bo Qu; Lijun Zhang (Plant Systematics and Evolution, 2013)

The melanocortin 1 receptor (MC1R) inhibits the inflammatory response in Raw 264.7 cells and atopic dermatitis (AD) mouse model - Wei Chen; Jianping Li; Hai’e Qu; Zhou Song; Zhanqing Yang; Jinlong Huo; Huaizhi Jiang; Qinghua Huang; Meixia Huo; Bo Liu; Qiaoling Zhang (Molecular Biology Reports, 2013)

A meta-analysis of β1-adrenergic receptor gene polymorphisms in idiopathic dilated cardiomyopathy - Bo Jin; Qu-Zhen Ge-Shang; Yong Li; Wei Shen; Hai-Ming Shi; Huan-Chun Ni (Molecular Biology Reports, 2012)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Structural feature and its significance of the northernmost segment of the Tertiary Biluoxueshan-Chongshan shear zone, east of the Eastern Himalayan Syntaxis - Bo Zhang; JinJiang Zhang; DaLai Zhong; XiaoXian Wang; JunFeng Qu; Lei Guo (Science China Earth Sciences, 2011)

Varied association of prothrombin G20210A polymorphism with coronary artery disease susceptibility in different ethnic groups: evidence from 15,041 cases and 21,507 controls - Bo Jin; Yong Li; Qu-Zhen Ge-Shang; Huan-Chun Ni; Hai-Ming Shi; Wei Shen (Molecular Biology Reports, 2011)

Re–Os and 40Ar/39Ar ages of the Jiguanshan porphyry Mo deposit, Xilamulun metallogenic belt, NE China, and constraints on mineralization events - Huaying Wu; Lianchang Zhang; Bo Wan; Zhiguang Chen; Peng Xiang; Franco Pirajno; Andao Du; Wenjun Qu (Mineralium Deposita, 2011)

17β estradiol induced ROS generation, DNA damage and enzymatic responses in the hepatic tissue of Japanese sea bass - Harikrishnan Thilagam; Singaram Gopalakrishnan; Hai-Dong Qu; Jun Bo; Ke-Jian Wang (Ecotoxicology, 2010)

Antifungal macrocyclic bis (bibenzyls) from the Chinese liverwort Ptagiochasm intermedlum L. - Chun-Feng Xie; Jian-Bo Qu; Xiu-Zhen Wu; Na Liu; Mei Ji; Hong-Xiang Lou (Natural Product Research, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

The promotion of clean development mechanism to cement industry capturing waste heat for power generation in China - Qishe Yan; Chang-Bo Zhou; Peng Qu; Rui-qin Zhang (Mitigation and Adaptation Strategies for Global Change, 2009)

Hypoglycemic Activity of Grifola frondosa Rich in Vanadium - Bo Cui; Linna Han; Jingran Qu; Yingtao Lv (Biological Trace Element Research, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Evidence for programmed cell death and activation of specific caspase-like enzymes in the tomato fruit heat stress response - Gui-Qin Qu; Xiang Liu; Ya-Li Zhang; Dan Yao; Qiu-Min Ma; Ming-Yu Yang; Wen-Hua Zhu; Shi Yu; Yun-Bo Luo (Planta, 2009)

Different roles of galectin-9 isoforms in modulating E-selectin expression and adhesion function in LoVo colon carcinoma cells - Feng Zhang; Minhua Zheng; Ying Qu; Jianfang Li; Jun Ji; Bo Feng; Aiguo Lu; Jianwen Li; Mingliang Wang; Bingya Liu (Molecular Biology Reports, 2009)

Introduction of a seedling production method using vegetative gametophytes to the commercial farming of Laminaria in China - Bo Xu; Quan Sheng Zhang; Shan Cun Qu; Yi Zhou Cong; Xue Xi Tang (Journal of Applied Phycology, 2009)

Comparison of Vanadium-Rich Activity of Three Species Fungi of Basidiomycetes - Chunchao Han; Bo Cui; Jingran Qu (Biological Trace Element Research, 2009)

Phosphate assimilation by Chlorella and adjustment of phosphate concentration in basal medium for its cultivation - Chun-Bo Qu; Zheng-Yun Wu; Xian-Ming Shi (Biotechnology Letters, 2008)

Role of Rac and Rho-GDI Alpha in the Frequency-dependent Expression of h1-calponin in Vascular Smooth Muscle Cells under Cyclic Mechanical Strain - Ming-Juan Qu; Bo Liu; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2008)

The Influence of Surface Trapping and Dark States on the Fluorescence Emission Efficiency and Lifetime of CdSe and CdSe/ZnS Quantum Dots - Hong-Mei Gong; Zhang-Kai Zhou; Hao Song; Zhong-Hua Hao; Jun-Bo Han; Yue-Ying Zhai; Si Xiao; Qu-Quan Wang (Journal of Fluorescence, 2007)

Cloning and Characterization of a Novel, Human Cellular Retinaldehyde-binding Protein CRALBP-like (CRALBPL) Gene - Ya-Hui Kong; Guang-Ming Ye; Kai Qu; Wen-Qi Pan; Xiang-Hua Liu; Bo Wan; Jin-Hu Guo; Long Yu (Biotechnology Letters, 2006)

The satellite-derived distribution of chlorophyll-a and its relation to ice cover, radiation and sea surface temperature in the Barents Sea - Bo Qu; Albert J. Gabric; Patricia A. Matrai (Polar Biology, 2006)

Weathering mechanism of the Cretaceous argillaceous siltstone caverns, Longyou, China - Gai-mei Guo; Li-hui Li; Zhi-fa Yang; Bo Tao; Yong-xin Qu; Jian Zheng (Bulletin of Engineering Geology and the Environment, 2005)

Establishment of a xylose metabolic pathway in an industrial strain of Saccharomyces cerevisiae - Ying Wang; Wen-Long Shi; Xiang-Yong Liu; Yu Shen; Xiao-Ming Bao; Feng-Wu Bai; Yin-Bo Qu (Biotechnology Letters, 2004)

Theoretical studies on the mechanism of primary electron transfer in the photosynthetic reaction center of Rhodobacter sphaeroides - Hong Xu; Ru-Bo Zhang; Shu-Hua Ma; Zheng-Wang Qu; Xing-Kang Zhang; Qi-Yuan Zhang (Photosynthesis Research, 2002)